Clinical and Preclinical Studies of Fermented Foods and Their Effects on Alzheimer's Disease - Muganti Rajah Kumar; Nor Farahin Azizi; Swee Keong Yeap; Janna Ong Abdullah; Melati Khalid; Abdul Rahman Omar; Mohd. Azuraidi Osman; Adam Thean Chor Leow; Sharifah Alawieyah Syed Mortadza; Noorjahan Banu Alitheen (MDPI AG, 2022)
The focus on managing Alzheimer's disease (AD) is shifting towards prevention through lifestyle modification instead of treatments since the currently available treatment options are only capable of providing symptomatic relief marginally and result in various side effects. Numerous studies have reported that the intake of fermented foods resulted in the successful management of AD. Food fermentation is a biochemical process where the microorganisms metabolize the constituents of raw food materials, giving vastly different organoleptic properties and additional nutritional value, and improved biosafety effects in the final products. The consumption of fermented foods is associated with a wide array of nutraceutical benefits, including anti-oxidative, anti-inflammatory, neuroprotective, anti-apoptotic, anti-cancer, anti-fungal, anti-bacterial, immunomodulatory, and hypocholesterolemic properties. Due to their promising health benefits, fermented food products have a great prospect for commercialization in the food industry. This paper reviews the memory and cognitive enhancement and neuroprotective potential of fermented food products on AD, the recently commercialized fermented food products in the health and food industries, and their limitations. The literature reviewed here demonstrates a growing demand for fermented food products as alternative therapeutic options for the prevention and management of AD.